2020
DOI: 10.1111/plb.13084
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of mTERF5 and mTERF9 contribution to salt tolerance, plastid gene expression and retrograde signalling in Arabidopsis thaliana

Abstract: We previously showed that Arabidopsis mda1 and mterf9 mutants, defective in the chloroplast-targeted mitochondrial transcription termination factors mTERF5 and mTERF9, respectively, display altered responses to abiotic stresses and abscisic acid (ABA), as well as perturbed development, likely through abnormal chloroplast biogenesis.• To advance the functional analysis of mTERF5 and mTERF9, we obtained and characterized overexpression (OE) lines. Additionally, we studied genetic interactions between sca3-2, aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(118 reference statements)
2
6
0
Order By: Relevance
“…As such, as these results show that both RPOTp-and PEP-mediated plastid transcription are involved in plant salt tolerance, we consider it feasible that PGE alteration at the transcriptional level may account for the abiotic stress phenotype of mutants sca3, mterf and sig5-2. Consistently with this, sca3-2 synergistically interacts with mutations mterf6-5 and mterf9 [31,49].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As such, as these results show that both RPOTp-and PEP-mediated plastid transcription are involved in plant salt tolerance, we consider it feasible that PGE alteration at the transcriptional level may account for the abiotic stress phenotype of mutants sca3, mterf and sig5-2. Consistently with this, sca3-2 synergistically interacts with mutations mterf6-5 and mterf9 [31,49].…”
Section: Discussionsupporting
confidence: 72%
“…We consider that the hypersensitivity to stress displayed by the sca3 mutants is due to impaired RPOTp function, and does not result from a delayed germination caused by the stress treatments. Consistent with this, other chloroplast-defective mutants, such as mterf9 [which also shows, like sca3 plants, stunted growth and impaired chloroplast biogenesis, and is morphologically very similar to sca3 (both mutations even interact synergistically)], display enhanced tolerance to abiotic stress [31,42]. As such, these results suggest that RPOTp promotes tolerance to environmental stress during germination and seedling establishment.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…By contrast, the family expanded to c. 30 members in higher plants (Babiychuk et al, 2011;Kleine, 2012;Zhao et al, 2014) and recent studies have suggested that this expansion has been accompanied by a functional diversification in RNA metabolism such as intron splicing and rRNA maturation in organelles (Hammani & Barkan, 2014;Hsu et al, 2014;Romani et al, 2015;Zhang et al, 2018). In addition to these studies, transcriptomic and physiological analyses conducted in Arabidopsis and crop species have highlighted the importance of mTERF genes for plant response to a variety of abiotic stresses (Zhao et al, 2014;Zhou et al, 2016;Xu et al, 2017;Robles et al, 2018;Nunez-Delegido et al, 2019). Nevertheless, only a handful of mTERF genes have been characterized molecularly and biochemically in plants to better understand their functional diversification.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, several of these genes are essential for embryo viability (11)(12)(13). Others have been linked to a variety of abiotic stress-responses (8,(14)(15)(16)(17) but how these genes trigger these responses in plants is not understood. Plant mTERFs are predicted to act in mitochondria or chloroplasts but knowledge about their roles in organelles is scarce.…”
Section: Introductionmentioning
confidence: 99%